2018
DOI: 10.1332/030557318x15296526896531
|View full text |Cite
|
Sign up to set email alerts
|

Elite capture of local participatory governance

Abstract: Elite capture is a major barrier to citizen engagement in local governance processes in many developing countries. Data from six case studies of development initiatives in Bangladesh show that, in spite of attempts by aid donors and others to ensure citizen participation, programmes are dominated by a nexus of local elites including MPs and bureaucrats. Local stakeholders do not understand the value that direct citizen participation can bring, and citizens are unaware of their rights and wary of challenging el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…This use of the community structures as representatives of the people, along with the assumed power they have, leaves the engagement strategy prone to elite capture. This is problematic, as elite capture inhibits citizen engagement in local governance processes (Waheduzzaman et al, 2018). During the study, most youths reported issues of favouritism where only those known to the WCPC members and community leaders are involved in engagement processes.…”
Section: City Levelmentioning
confidence: 97%
“…This use of the community structures as representatives of the people, along with the assumed power they have, leaves the engagement strategy prone to elite capture. This is problematic, as elite capture inhibits citizen engagement in local governance processes (Waheduzzaman et al, 2018). During the study, most youths reported issues of favouritism where only those known to the WCPC members and community leaders are involved in engagement processes.…”
Section: City Levelmentioning
confidence: 97%
“…Participation as a concept came to the lime light as a result of rising advocacy for the end of the top-down strategies and to promote bottom-top approaches to development, in favour of greater inclusion of the subjects of the development programmes (Waheduzzaman et al, 2018). These scholars further explained that participation is a social transformation mechanism, where the power of the implementing agency is transformed by civil society.…”
Section: B Community Participation and Public Healthmentioning
confidence: 99%
“…Also, in the academic discourse, advocacy of adopting bottom-top approaches to solving various community problems including promoting public health has been a popular and current trend. Moreover, extant sociological studies have affirmed the grand relevance of Community-Based Organisations (CBOs) in boosting development in general at the grassroots level (Waheduzzaman, Assaber, & Hamid 2018;Adegbola, 2011;Islam, 2016;Chowdhury et al, 2020;Olayiwola, 2011). Therefore, this study reviews a number of relevant available previous studies to highlight and emphasize the significance of community participation via CBOs, preferably the Landlords Association, in ensuring the efficiency of the set up institutional frameworks in low-income residential areas, in particular.…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical premise leads to the idea that the government is the actor that defines the incentives that promote collective action and public well-being. Thus, in the empirical realm, practical processes of citizens’ inclusion in decision-making are rarely undertaken (Malena, 2009; Waheduzzaman et al , 2018) and are marked by a lack of transparency and representativeness, hence a lack of legitimacy too. Thus, two significant causes limit collective action in a territory: failing to consider public opinion; and the government’s denial of the importance of social participation in governance, a fundamental principle of collective action (Vargas-Lama and Osorio-Vera, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%